2020
DOI: 10.18805/ijar.b-3902
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance, Hematology and Serum Biochemistry of Commercial Broilers Supplemented with Nano Selenium and other Anti-Stressors during Summer

Abstract: The aim of this study is to determine the effect of dietary supplementation of nano selenium on production performance in commercial broilers during summer stress. Dietary nano selenium was compared with other anti-stressors such as inorganic selenium, Vitamin E, Vitamin C, Betaine and 1% Glutamine. A total of 420 commercial broilers were divided into seven treatments with three replicates of 20 birds each and were supplemented with basal diet (control), inorganic Se (0.30 mg/kg), nano Se (0.15 mg/kg), Vit E (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Compared with those methods, physical method-irradiation has advantages including the purity of obtained SeNP samples and the capability of producing large volumes at a competitive price level. Concerning physical methods, it is reported that the high energy ball milling technique could create SeNPs with sizes of 37-85 nm [55], while the pulsed laser ablation synthesized particles with diameter of 60-100 nm [56,57]. Therefore, the synthesis of SeNPs by electron beam irradiation could be an efficient approach to lower the particle size, aiming to enhance the strength of bioactivities as previously reported [13,14,19].…”
Section: Discussionmentioning
confidence: 83%
“…Compared with those methods, physical method-irradiation has advantages including the purity of obtained SeNP samples and the capability of producing large volumes at a competitive price level. Concerning physical methods, it is reported that the high energy ball milling technique could create SeNPs with sizes of 37-85 nm [55], while the pulsed laser ablation synthesized particles with diameter of 60-100 nm [56,57]. Therefore, the synthesis of SeNPs by electron beam irradiation could be an efficient approach to lower the particle size, aiming to enhance the strength of bioactivities as previously reported [13,14,19].…”
Section: Discussionmentioning
confidence: 83%
“…The reason for this is that nanoselenium affects the growth of birds through the metabolism of thyroid hormones, which play an important role in growth, protein production and metabolism by increasing the active hormone Tryodothyronine (T3) and decreasing the hormone Tetraiodothyronine (T4), thereby improving feed conversion to promote growth and live weight gain [23,24]. Jamima et al [25] reported that adding 0.15 mg/kg of nanoselenium particles to the feed could improve the weight gain and live weight of broiler chickens. The reason for the improved performance of poultry treated with nano-selenium be due to biological activity, which can effectively help maintain cell function against oxidative stress and lipid peroxidation, improve immunity and better growth of broiler chickens [27,26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many methods to describe the structure of selenium polysaccharides, including high-performance gel permeation chromatography (HPGPC), gas chromatography (GC), HPLC, methylation, nuclear magnetic resonance (NMR), SEM and AFS ( Jamima et al, 2021 ; Luo et al, 2021 ). These methods have been performed to determine the molecular weight, glycosidic bond and molecular morphology.…”
Section: Detection and Characterization Of Seleniummentioning
confidence: 99%